Treatment of oncological and hematological diseases in HIV infection - S. V. Lushchevich; V. D. Litvinov (Онкогематология, 2023)
Oncological and hematological diseases associated with HIV infection continue to cause discussions among foreign and domestic researchers, clinicians, doctors, medical workers. The ongoing world globalization and modernization, environmental degradation have a detrimental effect on the health of citizens, which can be seen in virus mutations, high morbidity and a decrease in the social level in the Russian Federation and in the world. Oncological and hematological diseases associated with HIV infection are growing in the Russian Federation, but scientists do not stop at the results achieved, improving methods, treatment and therapy. As part of this study a statistical analysis of oncological and hematological diseases associated with HIV infection for 3 years (2019–2021) in Russia is carried out in order to trace the percentage of the medicine’s level, treatment’s effectiveness and deaths. A detailed analysis shows the decrease in deaths from HIV infection which pays attention the work of specialists in the Russian Federation.   The purpose of this study is to identify a key method for the treatment of oncological and hematological diseases in HIV infection in Russia.   The objective is to study the effectiveness of existing methods of treatment.   Research methods – clinical, functional, microbiological and morphological.